A thermal fluid mechanical model of stress evolution for wire feeding-based laser additive manufacturing. (September 2021) - Liang, Lvjie; Hu, Renzhi; Wang, Jingsheng; Huang, Anguo; Pang, Shengyong
Abstract: Wire feeding-based laser additive manufacturing (WFLAM), highlighting high flexibility and efficiency, is widely used in large-scale structures. However, the heat input accumulation and large-scale effect lead to severe stress and deformation in the large-scale structures. This paper presented a novel coupled thermal fluid mechanical model of stress evolution considering the molten pool fluid flow influence by combining the computational fluid dynamics (CFD) model and the finite element method (FEM) model. In the CFD model, the fluid flow and heat transfer are considered; in the FEM model, the thermo-elastoplastic theory is used based on the non-linear material parameters. An accurate mapping algorithm was proposed to transfer the volume of fluid (VOF) and the temperature value from the CFD data to the FEM mesh. This model could obtain a more accurate temperature field than the thermal-mechanical model with the regular heat source. Besides, the model could consider the influence of the shape on the stress accurately. The simulation results show the tensile stress on the root can be increased from 370 MPa to more than 800 MPa, with the influence of the sharp angle defects. At the sidewall, the influence of the surface angle on the residual Mises stress is around 1100 MPa/rad.